2006
DOI: 10.4103/0019-5545.31594
|View full text |Cite
|
Sign up to set email alerts
|

Failed suicide and deliberate self-harm: A need for specific nomenclature

Abstract: Background:Out of those who attempted self-harm and survived, many actually wanted to die and many did not. Presently, no distinctive nomenclature exists for these two groups, which causes difficulty in understanding as well as in management and research.Aim:To study whether there exist two such groups which are distinct and can be differentiated clinically.Methods:Seventy-eight persons who attempted self-harm were evaluated in detail by a psychiatrist. The data were recorded in an especially designed proforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 6 publications
1
25
0
1
Order By: Relevance
“…Divorcees and individuals who were separated accounted for about 3.4%, while widows and widowers comprised 4.3% of the total suicide victims. [21] In individual studies, some show higher attempted suicides among unmarried persons[37444572] while others show a higher rate among those who are married. [4647] Among attempters, men were more likely to be single and women, married.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Divorcees and individuals who were separated accounted for about 3.4%, while widows and widowers comprised 4.3% of the total suicide victims. [21] In individual studies, some show higher attempted suicides among unmarried persons[37444572] while others show a higher rate among those who are married. [4647] Among attempters, men were more likely to be single and women, married.…”
Section: Epidemiologymentioning
confidence: 99%
“…The attempts in this group were impulsive, of low intentionality and lethality, and most sought help after the attempt. [37]…”
Section: Other Risk Factorsmentioning
confidence: 99%
“…3 While high intent was seen in the arranged group than the love group in our study, Sarkar et al found in his study on attempters and selfharmers, in the former, the acts were thoughtful, intent and fatality was high, with less voluntary disclosure; the latter were emotionally unstable with personality difficulties, with impulsive, low intent and less lethal attempts, and most seeking rescue eventually. 55,56 In the studies by Pearson & Liu, 26 and Kamimura et al, 27 couple satisfaction rates were still good in 40% spouses. Similarly, in this study too, couple satisfaction moderated suicidal intent in arranged marriage, but only mildly in love marriage.…”
Section: Discussionmentioning
confidence: 96%
“…The risk of suicide is also increasing during adverse events such as lack of social support, aggravation of the disease, and gradual increase in the incidence of diabetes complications. The next risk factor may be easy access of patients to self-injury tools [36]. Suicide by injecting insulin is not uncommon in both nondiabetic and non-diabetic subjects.…”
Section: The Impact Of Diabetes On the Risk Of Suicidementioning
confidence: 99%